Automated estimate of fish abundance through the autonomous imaging device GUARD1. (October 2018) - Marini, Simone; Corgnati, Lorenzo; Mantovani, Carlo; Bastianini, Mauro; Ottaviani, Ennio; Fanelli, Emanuela; Aguzzi, Jacopo; Griffa, Annalisa; Poulain, Pierre-Marie
Graphical abstract: Highlights: A standalone imaging device for underwater image acquisition and processing is presented. An automated image recognition approach for the macro- and mega- fauna is presented. The automated recognition was assessed on a relevant image dataset. The potentiality of such a device within the Argo programme is discussed. Abstract: Many technologies have been developed for monitoring the ocean interior. Among them the monitoring approaches based on imaging devices are capable to disclose important data on species behaviour and spatio-temporal variations of richness and evenness. In this context, the Argo programme (http://doi.org/10.17882/42182 ) is a valuable instrument for monitoring the deep sea at global scale in space and time. Argo floats equipped with imaging devices are candidate to become a new monitoring tool for studying macro- and mega-fauna in large areas and for extended time periods, potentially providing monitoring results never attained before. This work summarises the results obtained on the automated fish recognition task performed on the images acquired by the GUARD1 imaging device 1 .